Effects of special educational needs and socioeconomic status on academic achievement. Separate or confounded?. (2022) - Lenkeit, Jenny; Hartmann, Anne; Ehlert, Antje; Knigge, Michel; Spörer, Nadine
Highlights: Theoretically, educational careers of SEN and low-SES students are very similar. Effects of SEN-LD and SEN-ESD are overall more predictive of achievement outcomes than SES for both younger and older students. Mediation effects of SES are found mainly for younger students, specifically for those with SEN-LD. SES and SEN remain largely independent risk factors for achievement status and growth. Low-SES students are more likely to be ascribed a SEN-ESD in high-SES classes. Abstract: Germany is continuously expanding its inclusive education system. Research provides evidence that students with special educational needs (SEN) in inclusive school settings show lower academic achievement and come from lower socioeconomic backgrounds than their peers without SEN. Identifying to what extent the disadvantages originating from both characteristics are confounded in predicting academic achievement, has been neglected in the German educational context. Using data of 1711 primary and secondary school students from a longitudinal study in the state of Brandenburg, this study evaluates to what degree SEN (in the areas of learning and emotional-social difficulties) and socioeconomic background (SES) are confounded in predicting academic initial achievement in reading and mathematics as well as their development over time. Using multilevel modelling techniques that nest three measurement points into students and students into classes, results identify SES and SEN as relevant predictors of achievement status and growth in both subjects. Only few and small mediation effects of SES were found, indicating that both SES and SEN remain independent risk factors for achievement. Understanding the origins of student disadvantage can help teachers to make better informed choices for designing support measures and aid policymakers' reasoning for resource allocations.